Adoption of woreda participatory land use planning in pastoral areas by the Government of Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2019)
Developed with technical support from ILRI, woreda (district) participatory land use planning (WLUP) is a government-led process specifically designed for Ethiopia’s pastoral areas and in which local communities are involved in land use planning. Following piloting in two woredas, the Government of Ethiopia adopted WLUP and launched a WLUP manual in September 2019.